EFFECT OF VANADIUM AND TITANIUM SUBSTITUTION OVER AN ANTIMONY-BASED MIXED OXIDE CATALYSTS FOR PROPANE AMMOXIDATION TO ACRYLONITRILE - Ramli, Anita; Abdul Hamid, Asna Rasyidah; Manaf, Faridah; Ibrahim, Suhaina M. (2007)
Antimony (Sb) oxide is known to be the active phase for the ammoxidation of propane to acrylonitrile (ACN). The influenced of V and/or Ti on the physicochemical properties of Sb-based mixed oxide catalysts were studied using catalysts prepared by slurry method. The dried precursor was calcined in air at 350-600 oC for a total of 10 h. The active phase in Sbpromoted catalysts were determined using X-ray Diffraction (XRD) while the changes in microstructure of these catalysts were studied using physical adsorption of nitrogen gas. The catalytic activity of these catalysts were tested in a fixed-bed reactor with online GC at 420 oC with reaction feed (%v) of 5.8:7:17.4 for propane, ammonia and oxygen, respectively. Results show that promotional of Sb with V and/or Ti has an effect on the chemical environment of the Sb-mixed oxide catalysts, leading to differences in catalytic activity of these catalysts.